Geschichtsbilder im postjugoslawischen Raum : Konzeptionen in Geschichtslehrbüchern am Beispiel von Selbst- und Nachbarschaftswahrnehmung - Karge, Heike 1970- (Internationale Schulbuchforschung, 1999)
This study is based on an analysis of the most recently issued textbooks used in the post-Yugoslavian region (excluding Slovenia). The focus is placed on analysing the way in which each nation presents its own national history and sowith invariably the history of other neighbouring nations. The purpose of this paper is, on the one hand, to complement the number of excellent studies which already exist regarding this particular theme in this region. On the other hand, the advantage of this analysis is that a wealth of examples could be included from the most recently published textbooks, thus adding to what is already known about how people in Balkan countries perceive themselves and others. This is in itself important for pointing out new incentives for historical paradigms of perception, especially in the Croatian and Bosnian-Herzegovian region.